HUBUNGAN TINGKAT PENGETAHUAN KELUARGA DENGAN UPAYA PENCEGAHAN KOMPLIKASI DIABETES MELLITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS BABAKAN KABUPATEN CIREBON - Lukatul Khoiriyah; Ramli Effendi; Thia Oktiany (LPPM ITEKES Mahardika, 2021)
The level of family knowledge is a very important factor in the actions of families of people with Diabetes Mellitus, behavior based on knowledge will be easier to carry out than those not based on knowledge. Diabetes Mellitus is a disease that requires proper and immediate treatment efforts because it can cause complications such as heart disease, kidney failure, and damage to the nervous system. One way to overcome the effects of Type 2 Diabetes Mellitus is by applying a diet. This study aims to determine the relationship between the level of family knowledge with efforts to prevent complications of type 2 diabetes mellitus in the work area of Babakan Puskesmas, Cirebon Regency. This research method uses descriptive correlational, this research uses cross section research. The population is all families with type 2 Diabetes Mellitus in the work area of Babakan Puskesmas in Cirebon Regency as many as 144 respondents and sampling using Purposive Sampling obtained 60 respondents. The instruments used were questionnaire sheets, and data analysis using chi-square test that is the significance value α = 0.1. The results of the above study indicate between the level of family knowledge and prevention of complications of type 2 diabetes mellitus in getting p-value = 0.04, because the p-value of 0.04 <0.1 then Ho is rejected and Ha is accepted which means there is a relationship between the level of family knowledge and prevention of complications of type 2 diabetes mellitus in the work area of Babakan Health Center, Cirebon Regency.